Advances in Middle Infrared Laser Crystals and Its Applications - Duan, Xiaoming; Dou, Renqin; Li, Linjun; Yang, Xiaotao (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
In the last twenty years, there has been a growing interest in middle infrared (mid-IR) laser crystals and their application to achieve mid-IR laser radiations, which has benefited from the development of novel mid-infrared crystals and the improving quality of traditional mid-IR crystals. Moreover, these works have promoted the development of related technical applications. This Special Issue of the journal Crystals focuses on the most recent advances in mid-IR laser crystals, from materials to laser sources and applications. It aims to bring together the latest developments in novel mid-IR crystals, improvements in the quality of mid-IR crystals, mid-IR non-linear crystals and mid-IR lasers, as well as the application of mid-IR technology in spectroscopy, trace gas detection and remote sensing, optical microscopy and biomedicine. Aspiring authors are encouraged to submit their latest original research, as well as forward-looking review papers, to this Special Issue.